Positional differences in match running performance of women soccer players - Kutnjak, M.; Bjelica, D.; Modric, T. (European Journal of Human Movement, 2023)
This study aimed to identify positional differences in the running performance (RP) of professional women soccer players. Seventy match performances were observed during the official matches (n = 13) over the course of half of a season at the highest level of national soccer competition in Slovenia. Players` RP were obtained using global positioning system technology and were classified into five playing positions: central defender (CD; n = 11), fullback (FB; n = 15), central midfielder (CM; n = 9), winger (WM; n = 25) and forward (FW; n = 10). RP variables included total distance, high-intensity running, high-metabolic load distance, high-intensity accelerations and decelerations, and maximal running speed. Univariate and multivariate differences in RP among playing positions were analyzed by one-way analysis of variance and discriminate canonical analysis, respectively. Significant univariate differences were found for all RP variables (f = 3.77 - 8.68, µ = 0.19 - 0.33). Specifically, WMs, FBs, and CMs covered more total distance than CDs or FWs. High-intensity running, high metabolic load distance, high-intensity accelerations, and decelerations were greater for FBs or WMs compared to the players in all other playing positions. Analysis of multivariate differences showed significant differentiation between FBs and CMs, CDs, and FWs in high-intensity running distance, high-metabolic load distance, and high-intensity decelerations (CanR= 0.4 - 0.77, all p < 0.01), respectively, with higher occurrence in FBs. These findings demonstrated the differing physical demands placed on national-level women's soccer players in different playing positions, offering valuable insights for their preparation.